2021
DOI: 10.1177/02698811211044679
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and noradrenergic modulation of stress-induced alterations in brain activation associated with goal-directed behaviour

Abstract: Background: Acute stress is thought to reduce goal-directed behaviour, an effect purportedly associated with stress-induced release of catecholamines. In contrast, experimentally increased systemic catecholamine levels have been shown to increase goal-directed behaviour. Whether experimentally increased catecholamine function can modulate stress-induced reductions in goal-directed behaviour and its neural substrates, is currently unknown. Aim: To assess whether and how experimentally induced increases in dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
(159 reference statements)
1
2
0
Order By: Relevance
“…Compared to the no-stress control protocol, the MAST induced significant autonomic responses including increases in systolic and diastolic blood pressure, and increases in cortisol, in both those which received psilocybin, and those that had received placebo. Such findings are in line with previous studies utilizing the MAST in a healthy population[40, 88-92]. In contrast to the previous studies whom also demonstrated a strong increase in subjective concentrations of state anxiety after the MAST, ratings of anxiety did not reach significance when comparing the stress to no stress condition.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the no-stress control protocol, the MAST induced significant autonomic responses including increases in systolic and diastolic blood pressure, and increases in cortisol, in both those which received psilocybin, and those that had received placebo. Such findings are in line with previous studies utilizing the MAST in a healthy population[40, 88-92]. In contrast to the previous studies whom also demonstrated a strong increase in subjective concentrations of state anxiety after the MAST, ratings of anxiety did not reach significance when comparing the stress to no stress condition.…”
Section: Discussionsupporting
confidence: 90%
“…As mentioned previously, the cingulate cortex and insula are involved in processing reward values (e.g. Alexander & Brown, 2019;Rolls, 2019) and have been observed to be affected by acute stress (van Ruitenbeek et al, 2021). Other areas like the amygdala and hippocampus are commonly known to regulate stress.…”
Section: Functional Imaging Studiesmentioning
confidence: 92%
“…MPH may therefore suppress reward value and diminish reward-based learning in SUD patients, which is in line with an MPH-induced reduction in functional connectivity between the nucleus accumbens and ventral pallidum (199) as a neural substrate for drug liking (200). Improved behavioral control is suggested by MPH-induced altered functional connectivity between the nucleus accumbens medial PFC (199), an area associated with reflective cognition (201). In addition, MPH reversed an acute stress-induced reduction in brain activation associated with goal-directed behavior (202).…”
Section: Current Evidence For Mph E Cacy In Sudmentioning
confidence: 99%